Paradigma Baru Belajar Sesuai Gaya Belajar Mahasiswa - Marojahan Saragi; Estherina Andhi Juniva (STT IKSM SANTOSA ASIH, 2024)
Abstract: The learning paradigm should be understood early on by a lecturer, teacher, student or student. This is to make it easier for each learning style and can apply the teaching style as well. This study aims to identify the learning/teaching styles of each learner. The research method used in this research is descriptive qualitative research. Qualitative research is research that produces descriptive data in the form of written or spoken words from people and observable behavior. Descriptive qualitative research is a methodology in examining the status of a group of people, an object, a set of conditions, a system of thought or a class of events in the present.The research was carried out at STT IKSM Santosa Asih Jakarta, on Monday, October 10 2022. The resource persons in this study were 56 students from the Odd Semester T.A. 2022/2023. Then the learning styles (gaya belajar) of 56 students were identified, as follows: Students of STT IKSM Santosa Asih Jakarta were studied, then there were 17% (as many as 9 people) with a